Mining Failure Response Characteristics of Stope Floor: A Case of Renlou Coal Mine - Jucai Chang; Dong Li; Kai He (Advances in Civil Engineering)
Currently, shallow coal resources are being exhausted gradually, mining depth is continuing to extend downward, and hydrogeological conditions are becoming increasingly complex. Therefore, accurate determination of the failure floor position is necessary to perform multiple-seam mining. In this study, the 7255 working face of the Renlou coal mine is regarded as the research object. Through a comprehensive measurement of ground penetrating radar detection and fixed-point grating optical fibers, the law of floor deformation and failure is analyzed dynamically, and the characteristics of the floor rock deformation response are discussed. The results of on-site monitoring indicate that the mining effect of the working face is greater than that of the tectonic stress. With the advance of the working face, the deformation of the shallow area (0–8 m) first increases gradually, then increases rapidly, and finally increases gradually again; the middle area (8–19 m) experiences three stages, from a gentle increase to temporary stability and then a rapid increase; the deep area (19–29 m) undergoes three stages, from being stable to increasing and then being stable again. After mining, the floor of the working face can be classified into four areas in the vertical direction: complete failure area (0–5 m), poor severe influence area (5–11 m), failure development area (11–19 m), and elastic deformation area (19–29 m). Mining-induced stresses cause resistance at the interface of different lithologies and weaken the effect of downward propagation. Coal seams and the interface between different lithologies are more prone to deformation. The results can provide a certain reference basis for the advanced exploration scheme of the underlying seam mining under the multiple-seam mining method, as well as provide a new approach for floor failure depth measurement.